Russian Federation : IOSCO Objectives and Principles of Securities Regulation - Britton, Richard (International Monetary Fund, Washington, DC, 2017)
An assessment of the level of implementation of the International Organization of Securities (IOSCO) principles in the Russian Federation was conducted from February 3 to 16, 2016 as part of the financial sector assessment program (FSAP) by Richard Pratt and Richard Britton, both external Monetary and Capital Markets Department experts. Central Bank of the Russian Federation (CBR) has created a three-year strategy on financial market development and stability; one of its goals for the period of 2016-18 is creating conditions for the growth of the financial industry. The assessment was conducted based on the IOSCO principles and objectives of securities regulation approved in 2010 and its methodology adopted in 2011 and updated in 2013. Principle 38 was not assessed since this principle is now covered under the principles for financial market infrastructures (PFMI). As a result, issues related to the central counterparties are not covered in this assessment.